2018
DOI: 10.1142/9789813227767_0010
|View full text |Cite
|
Sign up to set email alerts
|

The Development of MPI Modeling in Pythia

Abstract: Many of the basic ideas in multiparton interaction (MPI) phenomenology were first developed in the context of the Pythia event generator, and MPIs have been central in its modelling of both minimum-bias and underlying-event physics in one unified framework. This chapter traces the evolution towards an increasingly sophisticated description of MPIs in Pythia, including topics such as the ordering of MPIs, the regularization of the divergent QCD cross section, the impact-parameter picture, colour reconnection, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 174 publications
2
49
0
Order By: Relevance
“…From the theoretical side, there are calculations [23] that have been included in the PYTHIA event generator. This research area has gained more interest given that its development [24] helps to understand the non-perturbative QCD processes and could also be related to physics at the LHC energies.…”
Section: F − B Multiplicity Correlations Color Reconnection and Multmentioning
confidence: 99%
See 2 more Smart Citations
“…From the theoretical side, there are calculations [23] that have been included in the PYTHIA event generator. This research area has gained more interest given that its development [24] helps to understand the non-perturbative QCD processes and could also be related to physics at the LHC energies.…”
Section: F − B Multiplicity Correlations Color Reconnection and Multmentioning
confidence: 99%
“…It is thus concluded that the average of such events should contain hard interactions. An average above unit corresponds to more than one sub-collision per event, which is allowed by the multiple structure of the incoming hadrons, described by the following expression [24]:…”
Section: F − B Multiplicity Correlations Color Reconnection and Multmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the numerator in Eq. (31) is sensitive to DPS (or MPIs in general), we conclude that the good agreement here suggest that the inconsistencies observed in Figure 2 are indeed due to poorly-constrained charm fragmentation, rather than the MPI modelling in Pythia [72, 73,74]. The bottom panel of Figure 3 shows ratios…”
Section: P-p Collisionsmentioning
confidence: 52%
“…The second EEMC background is an estimate of the background caused by falsely attributing parts of jet particles to the neutrino's missing p T . Also included in the figure is the W -decay electron signal from a MC simulation (based on Pythia 6.4.28 [15] and GEANT [16]), and the sum of the signal and background contributions, which describes the measured E T distribution fairly well. When the final analysis cut requiring E T > 25 GeV is applied, there is little background contamination remaining relative to the W signal.…”
Section: Resultsmentioning
confidence: 99%